Manual propulsion mechanisms of vehicles for the locomotion of people with lower-limbs motor disabilities: prospective study (Research, Society and Development, 2022)
People with motor disabilities present mobility-related needs that the available products cannot fully meet. Widely adopted assistive devices, wheelchairs have low mechanical efficiency, therefore, not ideal for locomotion. The mechanisms developed to solve this fact still need attention in their project and do not deliver complete solutions. Other vehicles are used for this purpose more efficiently; however, they present inappropriate configurations. This study aims to search for technologies used in manual propulsion mechanisms used in vehicles for people with lower-limb motor disabilities. As a methodology adopted, a prospective study was carried out to verify the technological scenario. For the selection criteria adopted, 19 patents were found, none in Brazil, on the search platform. These results demonstrate that there is potential to work with product projects for this group in the country due to the market gap.